2023
DOI: 10.1007/s40520-023-02508-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load decreases with age and is associated with sagittal abdominal diameter: a nationally representative quantification study in US adults

Abstract: Background Dietary acid load (DAL) has been associated with frailty and hip fractures in older adults, who often have a reduced kidney function and thus compromised buffering capacities. Studies to quantify DAL in older adults are scarce and controversies persist as to whether DAL in- or decreases with age. Aim To enhance the understanding of DAL in older individuals, we examined its relationship with increasing age and selected anthropometric data in a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Te human kidneys, in contrast, can only excrete 40-70 mEq of acid within 24 h [50]. Once that limit is reached, acid is retained in the human body, with potentially harmful efects for human health [51][52][53][54][55][56]. As summarized in a previous review, dietary acid load has been linked to several cardiovascular disease risk factors, unfavorable metabolic alterations, diabetes, and chronic kidney disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…Te human kidneys, in contrast, can only excrete 40-70 mEq of acid within 24 h [50]. Once that limit is reached, acid is retained in the human body, with potentially harmful efects for human health [51][52][53][54][55][56]. As summarized in a previous review, dietary acid load has been linked to several cardiovascular disease risk factors, unfavorable metabolic alterations, diabetes, and chronic kidney disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…We use four well-established formulas as proxies for DAL based on a recent study. 16 First, we used the PRAL formula proposed by Remer et al which is based on daily intake of total protein and multiple minerals: 9 Subsequently, Frassetto et al 10 proposed a simplified formula for calculating DAL, ie, . Another NEAP formula is from Remer et al 17 where OA est is the anthropometrically estimated organic acid secretion, which is obtained from the body surface area× 41/1.73 (the body surface area was calculated by the formula of Dubois et al 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…We use four well-established formulas as proxies for DAL based on a recent study. 16 First, we used the PRAL formula proposed by Remer et al which is based on daily intake of total protein and multiple minerals: PRAL R mEq=day ð Þ¼ 0:49…”
Section: Definition Of Dalmentioning
confidence: 99%
“…In addition to BMI, several studies report a positive association between high DAL and various other anthropometric measurements. These include an increased waist-to-height ratio, larger hip and neck circumference, a higher fat mass, and lower fat-free mass [ 11 , 96 , 141 , 142 ]. Moreover, a study involving 3018 individuals aged 60 years and older from the USA identified that a high DAL is not only positively correlated with BMI but also with sagittal abdominal diameter [ 142 ].…”
Section: Dietary Acid Load In Metabolic Disordersmentioning
confidence: 99%
“…These include an increased waist-to-height ratio, larger hip and neck circumference, a higher fat mass, and lower fat-free mass [ 11 , 96 , 141 , 142 ]. Moreover, a study involving 3018 individuals aged 60 years and older from the USA identified that a high DAL is not only positively correlated with BMI but also with sagittal abdominal diameter [ 142 ]. This association was also found in a study in 456 children from Iran, which identified a positive association between a high DAL and a greater risk of childhood obesity, as defined by BMI and higher body fat percentage [ 141 ].…”
Section: Dietary Acid Load In Metabolic Disordersmentioning
confidence: 99%